PERLINDUNGAN HUKUM TERHADAP STATUS KEWARGANEGARAAN ANAK HASIL DARI PERKAWINAN CAMPURAN BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN - Widodo, Agnes Visca Hemaskesuma (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACT Marriage is a bond that shows the relationship between one person and another. With the existence of Law Number 12 f 2006 concerning citizenship of the Republic of Indonesia which imposes dual citizenship only until the child is 18 years old or married, after which he must choose one of the nationalities of his choice.The enactment of Law Number 12 of 2006 concerning citizenship where if a child wants to get legal protection of a country. What is the citizenship status of children resulting from mixed marriages according to law number 12 of 2006 concerning citizenship and how are the civil rights of children resulting from mixed marriages according to the legal system in Indonesia. The method in this study uses a normative juridical research method based on the sources of legal material that will be studied by the author. The sources of legal material used include legislation related to the legal issues being handled. Keywords: Mixed Marriage, Dual Citizenship